2016
DOI: 10.1080/03003930.2016.1181059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Public Procurement Performance Management Systems in Local Governments

Abstract: International audienceIncreasing the effectiveness, efficiency, and compliance of public procurement (PP) has become an ongoing concern for governments. Public administrations at different levels are realising that – in order for PP to fulfil its mission – appropriate control and diagnostic systems must be put in place. This study aims to investigate the architecture of PP performance measurement systems (PP-PMSs) in local governments, drawing on four case studies from Italy and four from Wales. The theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
28

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(99 citation statements)
references
References 91 publications
6
65
0
28
Order By: Relevance
“…57% of the respondents classified this metric as important. Patrucco et al [30] evaluated how effectiveness, efficiency and compliance to public procurement have become an important part of government concern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…57% of the respondents classified this metric as important. Patrucco et al [30] evaluated how effectiveness, efficiency and compliance to public procurement have become an important part of government concern.…”
Section: Resultsmentioning
confidence: 99%
“…Patrucco et al [30] evaluated how effectiveness, efficiency and compliance to public procurement have become an important part of government concern. Public institutions have come to the realization that appropriate controls and diagnostics are necessary to fulfill procurement performance.…”
Section: Values That Determine Procurement Performance Measurementmentioning
confidence: 99%
“…The first strength of the methodology adopted in this paper is the use of a quantitative and comprehensive approach in the study of public procurement efficiency. The majority of publications in this field are either theoretical 53 or case-based and partial, 54 which makes comparisons and rankings rather difficult, if not impossible. However, this also creates a limitation.…”
Section: Resultsmentioning
confidence: 99%
“…However, public sector procurement is different from private procurement, so performance indicators will be different for the two areas. Patrucco et al (2016) identified areas for benchmarking state and municipal procurements containing performance criteria: 1. Budget savings; 2.…”
Section: Literature Review and Methodological Approachmentioning
confidence: 99%